Enhanced discolouration of methyl violet 10B in a gliding arc plasma reactor by the maghemite nanoparticles used as heterogeneous catalyst. Issue 2 (June 2015) - Tiya-Djowe, Antoine; Acayanka, Elie; Lontio-Nkouongfo, G.; Laminsi, Samuel; Gaigneaux, Eric M.
Graphical abstract: Abstract: This study focuses on the discolouration of a triphenylmethane dye (i.e. methyl violet 10B) using a gliding arc plasma discharge in humid air. The results show that the discolouration process is strongly dependent on the initial dye concentration. The maximum discolouration rates are 96.9% and 6.7% after 60 min for initial dye concentrations of 2.5 mg L −1 and 100 mg L −1, respectively. The incorporation of maghemite (γ-Fe2 O3 ) into a 100 mg L −1 dye solution increases the discolouration rate under plasma up to 55.6%. This improvement of the discolouration efficiency suggests that maghemite acts as a heterogeneous catalyst for Fenton decomposition of H2 O2 resulting from the dimerization of HO radicals produced by plasma in the gas phase. The X-ray diffraction (XRD) and Fourier transform-infrared (FTIR) characterizations of the catalyst before and after being used 3-times show that the maghemite nanoparticles are stable in the target-solution exposed to gliding arc plasma and can be therefore reused for further treatments.